Efficacy, safety, and tolerability of soticlestat (TAK-935) as adjunctive therapy in pediatric patients with dravet syndrome and Lennox–Gastaut syndrome: a meta-analysis of 3 randomized controlled trials - Lanlan, Zhang; Nana, Jiang; Chengzhong, Wang (Frontiers in Pharmacology, 2025)
PurposeTo evaluate the efficacy, safety, and tolerability of soticlestat as adjunctive therapy in pediatric patients with epileptic encephalopathies of Dravet syndrome (DS) and Lennox-Gastaut syndrome (LGS).MethodWe performed a computerized literature search of MEDLINE, EMBASE, Cochrane Library, Web of Science, Google Scholar, and ClinicalTrials.gov to identify eligible randomized, placebo-controlled trials (RCTs) until December 2024. We calculated risk ratios (RRs) for efficacy of responder rate, and tolerability profiles in terms of serious adverse event (SAE) and dropout for adverse events as well as the most common side effects. Quality assessment of included RCTs was performed using the Cochrane Collaboration tool.ResultsA total of 3 RCTs with 553 patients were included in the current study. Pooled RR for responder was 3.88 (95% CI 1.78–8.49, P = 0.001) among patients with DS, and for patients with LGS was 1.56 (95% CI 0.91–2.68, P = 0.11). Significantly more patients receiving soticlestat experienced discontinuation than placebo (RR 2.82 1.49–5.33, P = 0.001) because of adverse events. No significant difference in SAE was observed between the two treatment groups with RR 0.87 (95% CI 0.55–1.39, P = 0.57). Among the most common AE, only constipation occurred more often in the soticlestat group (RR 3.71, 95% CI 1.22–11.31, P = 0.02).ConclusionSoticlestat showed significantly higher efficacy in reducing convulsive seizures in patients with DS. Nonetheless, for patients with LGS, the difference between soticlestat and placebo was not statistically significant. The incidence of SAE in patients receiving soticlestat was similar to those receiving placebo; however, substantially more patients allocated to soticlestat discontinued prematurely because of side effects.